학령기 고기능 자폐의 음운재부호화 및 음운부호화 특성에 대한 연구 - 김화수(Wha Soo Kim); 이숙(Suk Lee); 조지숙(Ji Sook Cho); 양한나(Han Na Yang); 안수연(Su Yeon An) (언어치료연구, 2018)
목적: 본 연구는 학령기 고기능자폐학생과 일반학생을 대상으로 음운재부호화 및 음운부호화의 특성을 알아보고자 하였다. 방법: 본 연구에서는 학령기 고기능자폐학생 15명과 어휘연령을 일치시킨 학령기 정상학생 15 명을 대상으로 KC-TOPA-C 초등학생용을 실시하였다. 결과: 첫째, 음운재부호화와 음운부호화의 전체 문항에서 집단간 차이가 있는지 분석한 결과, 전체 과제에서 고기능자폐학생 집단과 일반학생 집단이 유의미한 차이를 보였다. 둘째, 연령간 음운재부호화, 음운부호화 차이를 분석한 결과, 고기능자폐 학생과 일반학생 7세집단, 8세 집단, 9세 집단 모두에서 유의미한 차이를 보였다. 셋째, 음운재부호화 과제에서 7세 집단의 고기능자폐학생들은 일반학생보다 색깔이름과 글자를 장기기억에서 인출하는 데 더 오랜 시간이 걸렸으며, 8세집단 역시 고기능자폐학생이 숫자 빨리 말하기와 글자 빨리 말하기 과제에서 유의미하게 느린 속도를 보였다. 또한, 9세 집단의 고기능자폐학생들은 글자 빨리 말하기 과제에서 일반학생들과 비교하여 가장 큰 차이를 보이는 것으로 나타났다. 음운부호화과제에서 7세 집단은 숫자 따라 말하기와 무의미 따라 말하기 순으로, 8세, 9세 집단에서는 무의미 따라 말하기, 숫자 따라 말하기 순으로 차이가 나타났다. 결론: 고기능자폐 학생은 어휘연령을 일치시킨 일반학생에 비해 음운재부호화와 음운부호화 능력이 떨어지는 것으로 나타났다. 또한, 고기능자폐학생은 일반학생에 비해 장기기억에서 인출하는 속도가 느리므로 읽기 및 쓰기와 관련한 교육에 있어서 충분한 반응 시간을 제시할 필요가 있으며, 단기기억폭이 일반학생에 비해 떨어지므로 어휘연령에 따라적절한 기억폭을 제시하여 이해를 증진시킬 필요가 있을 것이다. Purpose: This study intends to investigate characteristics of phonological coding and phonological recoding on school-aged high-functioning autistic and school-aged normal students. Method: This study was conducted on 15 high-functioning autisc and 15 normal students who matched for vocabulary age. The experiment was conducted on elementary school students in KC-TOPA-C. Results: First, there was a difference between the groups of high-functioning autistic students and general students in the overall task. Second, the difference of phonemic recoding and phonological coding between the ages showed that there was a difference between the high-functioning autistic students and the general students aged 7-9. Third, the high-functioning autistic students of the 7-year-old group took longer to withdraw color names and letters from long-term memory than the general students. The high-functioning autistic students in the 9-year-old group showed the biggest difference in the rapid letter elicitation task. In the phonological coding task, the 7-year-old group showed differences among the groups in order of repetition of numbers and repetition of non-words. For students between the ages of 8 and 9, there was a difference in the order of repetition of non-words, which was greater than repetition of numbers. Conclusion: The high-functioning autistic students showed less phonological recoding and phonological coding ability than general students who matched vocabulary age. High-functioning autistic students are more likely to withdraw from long-term memory than regular students, so it is necessary to provide sufficient response time for reading and writing. As short-term memory is lower than that of general students, it may be necessary to improve understanding by presenting adequate memory. KCI Citation Count: 1